2015
DOI: 10.1074/mcp.m113.035089
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals a Role for Epigenetic Reprogramming During Human Monocyte Differentiation

Abstract: The differentiation of monocytes into macrophages and dendritic cells involves mechanisms for activation of the innate immune system in response to inflammatory stimuli, such as pathogen infection and environmental cues. Epigenetic reprogramming is thought to play an important role during monocyte differentiation. Complementary to cell surface markers, the characterization of monocytic cell lineages by mass spectrometry based protein/histone expression profiling opens a new avenue for studying immune cell diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
1
18
0
1
Order By: Relevance
“…In support of a causal relationship between linker histone occupancy and H3 modifications, overexpression of linker histones caused a global reduction of core histone acetylation (Gunjan et al, 2001). Besides, a recent proteomic study revealed that downregulated expression of linker histones is correlated with generally elevated H3 modifications (Nicholas et al, 2014).…”
Section: H3 Tail Modifications and Linker Histone Occupancy Segregatementioning
confidence: 99%
“…In support of a causal relationship between linker histone occupancy and H3 modifications, overexpression of linker histones caused a global reduction of core histone acetylation (Gunjan et al, 2001). Besides, a recent proteomic study revealed that downregulated expression of linker histones is correlated with generally elevated H3 modifications (Nicholas et al, 2014).…”
Section: H3 Tail Modifications and Linker Histone Occupancy Segregatementioning
confidence: 99%
“…It is unclear whether epigenetic modifications induced by M. tuberculosis are restricted to myeloid precursors or whether they can also occur in differentiated monocytes. Again, in vitro evidence suggests that the late developmental switch from differentiated human CD14 + monocytes into either macrophages or DCs is directed by epigenetic changes (40). We found previously that in GM-CSF differentiated BM-MD-SC cultures, transcriptional and translational changes occur that are prerequisite for their development into M-MDSCs (21).…”
Section: Discussionmentioning
confidence: 85%
“…Hence, thanks to this biological setup, it is possible to study molecular changes linked to differentiation both as result of chemical stimulation and as result of physical stimulation by PEMF. Furthermore, because primary tissue macrophages cannot be readily expanded ex vivo, differentiation of monocytes from primary leukemia cell lines into macrophage-like cells has been frequently used as a mimic model for understanding the process of innate and adaptive immune responses to inflammatory stimuli [57,58].…”
Section: Discussionmentioning
confidence: 99%